Inuit Identities, Language, and Territoriality - Patrick, Donna (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2008)
AbstractThis paper provides a framework for understanding the social complexity of the linkages between language, identity, and territoriality (or attachments to place). Drawing on qualitative research among Inuit in the Canadian Arctic and in Ottawa, it discusses Inuit identities in relation to the role played by local, regional, national, and global processes in constructing Inuitness and the transformation of Indigenous identities nationally and globally. The paper argues that although Inuktitut is being supported by institutional and political structures in Nunavik and Nunavut, English and French have become increasingly important in daily Northern life. At the same time, Inuit migration to Southern cities has offered new challenges and established new priorities in the fostering of the plurilingualism necessary for urban Inuit life.